Sodium Dodecyl Sulfate-Modified Fe2O3/Molecular Sieves for Removal of Rhodamine B Dyes - Adnan A. AbdulRazak; Sohrab Rohani (Advances in Materials Science and Engineering)
Studying the removal of rhodamine B (RB) dye by using zeolite 13X molecular sieves supported by Fe2O3 nanoparticles (denoted as Fe2O3-13X) is the main objective of this study. Fe2O3-13X was synthesized and modified by the addition of sodium dodecyl sulfate (SDS). The prepared Fe2O3-13X was characterized by XRD, TEM, SEM, and zeta potential. The effects of the solution pH, SDS amount, contact time, initial dye concentration, and adsorbent dosage on the removal efficiency of RB were studied. A maximum removal efficiency of 99.3% was achieved. The adsorption equilibrium data of RB were fitted using the Freundlich model, yielding the maximum adsorption capacity of 89.3 mg/g. The findings revealed that the RB adsorption onto Fe2O3-13X modified with SDS (Fe2O3-13X-Ms) was described by a pseudo-second-order kinetic equation. The results reported in this paper indicate that a high RB removal percentage was attained by adding SDS to Fe2O3-13X.